Karakuri: A Proposal to Waste Reduce in the Health Service (Revista do LabDGE - UFF, 2023)
The objective of this study is to analyze the adherence of the Karakuri (low-cost automation) technology for eliminating Lean wastes in healthcare units. To carry out this study reports of continuous improvement practices were analyzed from three Units located in the State of São Paulo (Brazil). These practices of Lean Healthcare approach implementation were applied during the period from June to October 2020. The present literature on the term Karakuri was also analyzed in four data research bases and it was made a study around correlate cases. In conclusion, it is noted that Karakuri seems capable of eliminating the main wastes reported in the analyzed health units in question, which are: defects, motion, waiting, and not using human talent.